Careers in international affairs (Georgetown University Press, 2014)
This is the essential resource and job-hunting guide for all those interested in international careers in the US government, multinational corporations, banks, consulting companies, international and nongovernmental organizations, the media, think tanks, universities, and more. Careers in International Affairs, now in its ninth edition, provides up-to-date insights about the range of possibilities in the global workplace and tips on how to get these jobs―along with profiles of hundreds of important employers.